On the Relationship Between the Fractional Sumudu Transform and Fractional Fourier Transform - Saeed , Sadaf; Iqbal , Saleem; Sarwar , Farhana; Rehman, Abdul (American Scientific Research Journal for Engineering, Technology, and Sciences, 2020)
In this paper we have discussed fractional Sumudu transforms and its relationship with fractional Fourier transform and obtained the mathematical expression of kernel of fractional Sumudu transform. Such findings will play a significant role for fractional Sumudu transform to recognize its importance in the fields of engineering and applied mathematics like other fractional transforms.